Selection of marine type air compressor by using fuzzy VIKOR methodology - Kaya, Ahmet; Bashan, Veysi; Ust, Yasin (SAGE PUBLICATIONS LTD, 2022)
Ships have to maintain many auxiliary machineries with high power consumption, and these machineries generally run continuously for long hours. One of the auxiliary machineries that consume a lot of power in ships is the air compressor. These air compressors are especially important as they are used at the start of the main engine and generator diesel engines. Therefore, a suitable selection of these compressors is vital, in terms of technical requirement, energy efficiency, and cost effectiveness. The main focus of this study is to decide the optimum compressor in terms of all technical and operational criteria. In this context, using the fuzzy VIKOR method, five different and worldwide known compressor brands are listed in terms of selection by evaluating seven different and important criteria. These criteria were evaluated by five experts working as technical directors in shipping companies without being informed of each other. Briefly, this study aims to assist shipping companies in choosing the optimal compressor to suit their primary operating goals, considering the navigating routes and conditions of commercial ships. We believe that it is possible to close this gap in the literature and to select the optimum compressor according to the technical and operational needs.
Keywords: Compressor selection; fuzzy VIKOR; ship; starting air system; CRITICAL OPERATIONAL FAULTS; COMPROMISE SOLUTION; ENERGY; DECISION; AHP; RISK; EFFICIENCY; Engineering